Experience of European Clusters in Transsectoral Internationalization - Utkin, V. (Економічний вісник Донбасу, 2022)
This article discusses the importance of clusters in the modern economy as drivers of economic development, innovation, export, and better integration into international chains. The innovation cluster is a key element of the national (regional) innovation ecosystem, and the INNO Industry project aims to improve innovation development policies by involving clusters in Industry 4.0. The European Cluster Collaboration Platform is the main information tool for businesses in EU countries, offering opportunities for strengthening the European economy through the cooperation of industry cluster ecosystems. This platform allows any cluster initiative to be registered as a cluster organization, participant, or European cluster partnership, making it easy to find business partners for each country, region, sector or industrial ecosystem.
Discusses the factors that affect the competitiveness of a cluster, which can be categorized as internal and external. The internal factors include material and technical support of production, management tactics and strategy, innovation, pricing policy, competitiveness of products, labor resources, employee motivation, and modern information technologies. On the other hand, external factors include market conditions, logistics infrastructure development, social, environmental, scientific, technical factors, and labor market situations. The abstract also highlights the stable or long-term objective factors such as geographic concentration, climatic conditions, availability of natural resources, regional and national characteristics that can influence the competitiveness but cannot increase it by themselves. Understanding and managing these factors can help improve the competitiveness of a cluster. У статті обговорюється важливість кластерів у сучасній економіці як драйверів економічного розвитку, інновацій, експорту та кращої інтеграції в міжнародні ланцюги. Інноваційний кластер є ключовим елементом національної (регіональної) інноваційної екосистеми, а проєкт INNO Industry спрямований на вдосконалення політики розвитку інновацій шляхом залучення кластерів до Індустрії 4.0. Європейська платформа кластерної співпраці є основним інформаційним інструментом для бізнесу в країнах ЄС, що пропонує можливості для зміцнення європейської економіки через співпрацю галузевих кластерних екосистем. Ця платформа дозволяє зареєструвати будь-яку кластерну ініціативу як кластерну організацію, учасника або європейське кластерне партнерство, що полегшує пошук ділових партнерів для кожної країни, регіону, сектору чи промислової екосистеми.
Обговорюються фактори, що впливають на конкурентоспроможність кластера, які можна класифікувати як внутрішні та зовнішні. До внутрішніх факторів належать матеріально-технічне забезпечення виробництва, тактика і стратегія управління, інноваційна діяльність, цінова політика, конкурентоспроможність продукції, трудові ресурси, мотивація працівників, сучасні інформаційні технології. З іншого боку, зовнішні фактори включають ринкові умови, розвиток логістичної інфраструктури, соціальні, екологічні, наукові, технічні чинники та ситуацію на ринку праці. Анотація також висвітлює стабільні або довгострокові об’єктивні фактори, такі як географічна концентрація, кліматичні умови, наявність природних ресурсів, регіональні та національні особливості, які можуть впливати на конкурентоспроможність, але не можуть підвищити її самі по собі. Розуміння цих факторів і керування ними може допомогти підвищити конкурентоспроможність кластера.